2014
DOI: 10.1002/cncr.28869
|View full text |Cite
|
Sign up to set email alerts
|

Interferon‐γ–induced inflammatory markers and the risk of cancer: The Hordaland Health Study

Abstract: BackgroundIt has been reported that interferon-γ (IFN-γ)–induced inflammatory markers, such as circulating neopterin and kynurenine-to-tryptophan ratio (KTR), are increased in patients with cancer and are also a predictor of poor prognosis. However, whether baseline levels of these makers are associated with subsequent cancer risk in the general population remains unknown.MethodsWe conducted a prospective analysis of the Hordaland Health Study in 6594 adults without known cancer at baseline who were enrolled b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 45 publications
4
29
0
Order By: Relevance
“…Increased serum indoleamine 2,3‐dioxygenase (IDO), a rate‐limiting enzyme for tryptophan catabolism to kynurenine, is observed in HCC‐associated diseases, such as chronic hepatitis infection and obesity . Kynurenine/tryptophan ratio has been used as an indicator of IDO activity and was associated with increased risk of lung and overall cancers . Depletion of tryptophan and accumulation of kynurenine may suppress antitumor immune responses in chronically inflamed organs leading to activation of carcinogenesis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased serum indoleamine 2,3‐dioxygenase (IDO), a rate‐limiting enzyme for tryptophan catabolism to kynurenine, is observed in HCC‐associated diseases, such as chronic hepatitis infection and obesity . Kynurenine/tryptophan ratio has been used as an indicator of IDO activity and was associated with increased risk of lung and overall cancers . Depletion of tryptophan and accumulation of kynurenine may suppress antitumor immune responses in chronically inflamed organs leading to activation of carcinogenesis .…”
Section: Discussionmentioning
confidence: 99%
“…46 Kynurenine/tryptophan ratio has been used as an indicator of IDO activity and was associated with increased risk of lung 22 and overall cancers. 47 Depletion of tryptophan and accumulation of kynurenine may suppress antitumor immune responses in chronically inflamed organs 43 leading to activation of carcinogenesis. 48 Increased activity of this pathway can be particularly detrimental in liver microenvironment characterised by unique immunoregulatory functions and high level of expression of dioxygenases.…”
Section: Discussionmentioning
confidence: 99%
“…Accelerated breakdown of tryptophan and increased production of neopterin were found to parallel the course of different malignant diseases and predicting poor prognosis . Moreover, elevated baseline plasma neopterin levels and KTR were associated with a significantly higher risk of developing cancer in the general population …”
mentioning
confidence: 98%
“…(9) Moreover, elevated baseline plasma neopterin levels and KTR were associated with a significantly higher risk of developing cancer in the general population. (10) However, the diagnostic and prognostic role of IFN-cinduced inflammatory markers focusing on PCa is still unclear. The aim of this pilot study was to determine serum levels of neopterin and tryptophan breakdown in newly diagnosed PCa patients before RP and to test their relation to BCR after RP and prognosis (CSS).…”
mentioning
confidence: 99%
“…One previous epidemiological study observed an association between KTR and higher risk of lung cancer . A second prospective study showed associations between KTR or neopterin and risk of cancer overall, but no association was observed for risk of lung cancer specifically, possibly due to lack of statistical power . In addition, the downstream metabolites of the kynurenine pathway such as quinolinic acid (QA) have immuno‐regulatory effects and may contribute to the development and progression of lung cancer, but has not been investigated in large epidemiological studies.…”
Section: Introductionmentioning
confidence: 99%